Risk Factors of Neovascular Glaucoma After 25-gauge Vitrectomy for Proliferative Diabetic Retinopathy with Vitreous Hemorrhage: A Retrospective Multicenter Study - Takayama, Kei (Sci Rep, 2019)
Neovascular glaucoma (NVG) is a terminal severe complication in eyes with proliferative diabetic retinopathy (PDR), and PDR eyes with vitreous hemorrhage (VH) which undergo vitrectomy may have higher risk of postoperative NVG. The incidence and the prognostic factor of postoperative NVG after 25-gauge vitrectomy with advanced surgical options remain unclear. We retrospectively reviewed medical records of 268 eyes of 268 consecutive PDR patients with VH who underwent 25-gauge vitrectomy and 12 months follow-up at seven centers. Preoperative ocular factors (visual acuity, tractional retinal detachment, panretinal photocoagulation [PRP]), demographics and clinical factors (sex, age, diabetic duration, HbA1c, hypertension, anticoagulant medication, and kidney function), surgical procedures, and postoperative complications were compared between patients who developed postoperative NVG (9.3%) and those who did not. NVG eyes was significantly younger (P = 0.026), had shorter diabetic duration (P = 0.022), higher HbA1c (P = 0.028), absence of PRP (P = 0.039) and higher frequency of postoperative VH (P = 0.0075) than non-NVG eyes. Logistic regression analysis identified postoperative VH (P = 0.014), shorter diabetic duration (P = 0.029), and no PRP (P = 0.028) as prognostic factors for postoperative NVG. This multicenter study indicates that younger age, uncontrolled diabetes, no PRP, and postoperative VH are risk factors of post-vitrectomy NVG.